Feminism's progress : gender politics in British and American literature and television since 1830 - Colatrella, Carol (Albany : State University of New York Press, 2023)
"Explores how popular novels, short stories, and television shows from the United States and Britain illustrate the positive effects of feminism and promote gender equity"--
Justice and Revenge -- Hunting Criminals -- Chapter 7 Feminist Politics in Fiction -- Countering Expectations -- Feminist Ethics in Politics -- Family Problems -- Ethics and Democracy -- Madam President -- Femininity and Feminism -- Optimistic Feminism -- The Power of Feminist Narratives -- Epilogue -- Pandemic Problems -- Racial Disparities and Protests -- Backlash and Resistance -- Inclusion and Aspiration -- What Next? -- Notes -- Bibliography -- Index
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Feminism -- History -- 21st century; Equality; Women -- Social conditions -- 21st century; Sex discrimination against women; Television and women; Women in literature; Féminisme -- Histoire -- 21e siècle.; Femmes -- Conditions sociales -- 21e siècle.; Discrimination à l'égard des femmes; Télévision et femmes; Femmes dans la littérature.; SOCIAL SCIENCE / Women's Studies; Equality; Feminism; Sex discrimination against women; Television and women; Women in literature; Women -- Social conditions; History